Konsep Pendidikan Islam Menurut KH. Hasyim Asy’ari - Muhamad Faiz Amiruddin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2018)
Understanding A personal of KH. Hasyim Ash'ari. As one part of the traditionalist organization (NU), which is assumed to be the organization of the old-fashioned and illiterate people is an interesting thing to do. This is because he which is the background of pesantren life who never had the opportunity to endure a formal education, it has an unceasingly progressive thinking style for the size of the period in the framework of islamic boarding. Progressiveism of KH. Hashim Ash'ari thinking was initially considered to be against the traditions of islamic boarding and even considered to attempt to confuse religion and the world. This study aims to reveal the concept of Islamic education KH. Hasyim Ash'ari, with the focus of research include: (1) The concept of Islamic education KH. Hasyim Asy'ari, (2) Relevance of Islamic Education Concept KH. Hasyim Asy'ari with the Indonesia education today. Research methods or approach used in this paper is the research library (library research), the research activities undertaken by collecting data from various existing literature. With these techniques the author collects data written relics such as archives, books about opinions, theories relating to the study. In this study that the concept of Islamic education according to KH. Hasyim Ash'ari is tool and strategic effort undertaken by human beings in order to achieve humanity, so as to know the nature of its creation, its creator and the duties and responsibilities of humans as the caliph on tha earth which is the aims to with Islamic education, humans are able to get closer to Allah SWT , and also remain based on the Qur'an and Hadith. Learners should also have good behavior in learning, and an educator must also have pedagogical, personality, social and professional competence. Islamic Education System KH. Hasyim Asy'ari remains relevant in the context of Indonesia today. The education system is inclusive, adaptive, responsive and still strives to maintain the tradition in order to elevate the existence of Islam.